2015
DOI: 10.1007/s13361-015-1093-2
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Dissociation of the Interstrand i-Motif by the Sequences d(XnC4Ym) Monitored with Electrospray Ionization Mass Spectrometry

Abstract: Abstract. Formation and dissociation of the interstrand i-motifs by DNA with the sequence d(X n C 4 Y m ) (X and Y represent thymine, adenine, or guanine, and n, m range from 0 to 2) are studied with electrospray ionization mass spectrometry (ESI-MS), circular dichroism (CD), and UV spectrophotometry. The ion complexes detected in the gas phase and the melting temperatures (T m ) obtained in solution show that a non-C base residue located at 5′ end favors formation of the four-stranded structures, with T > A >… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 62 publications
1
22
0
Order By: Relevance
“…MS spectra showed abundant tetramolecular ions of d(TC 5 T) (including [4M] 5− at m/z 1592.69 and [4M] 4− at m/z 1991.12) in pH 4.5 NH 4 OAc buffer, containing 50 mM NH 4 + . These tetrameric species disappeared when the solution pH was adjusted to 9.0, indicating the formation and dissociation of tetrameric i-motifs (Supplementary Figure S1a and b) in accordance with our previous results (37). …”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…MS spectra showed abundant tetramolecular ions of d(TC 5 T) (including [4M] 5− at m/z 1592.69 and [4M] 4− at m/z 1991.12) in pH 4.5 NH 4 OAc buffer, containing 50 mM NH 4 + . These tetrameric species disappeared when the solution pH was adjusted to 9.0, indicating the formation and dissociation of tetrameric i-motifs (Supplementary Figure S1a and b) in accordance with our previous results (37). …”
Section: Resultssupporting
confidence: 92%
“…Specifically, the tetrameric ions ([4M] 7− at m/z 1499.36, [4M] 6− at m/z 1749.36 and [4M] 5− at m/z 2099.42) in the MS spectra (Supplementary Figure S2a and b) and the CD maximum at 288 nm and minimum at 265 nm (Supplementary Figure S2c) all indicate the presence of i-motif tetramers (47) and that they are more prominent in d(TGTC 5 T). We have previously demonstrated that short C-rich strands facilely form duplexes with C•CH + pairs under acidic condition and can be observed along with tetrameric i-motifs (37). Consequently, the low-abundance duplex ions observed here are mainly C•CH + -containing duplexes (C-duplex) since there are insufficient complementary G and C bases between two oligonucleotides to create WC duplexes (Supplementary Figure S2a and b).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations